Multikulturalisme: Re-imagining Agama - Gadis Arivia (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2005)
The foundation of multiculturalism, based on identities created from free choices, assumes that firstly, religion must be viewed as a cultural construct, a reality originating from various texts that seek to create new meanings and imaginations. In a society where multiculturalism is not embraced, the resulting form of society is communalism. Such a society prioritizes identity politics (identity recognition) over difference politics (pluralism recognition).